A study of benign breast disease management based on clinical, radiological and pathological assessment - Kanumuri, Sravanthi; Chalamalasetty, Jaya Durga; Reddy, A. Suryaprakash; Punyapu, Sridhar; Damam, Raghavendra; Sri, Narella Vasumathi Sai Lakshmi (ScienceRise: Medical Science, 2022)
Benign breast disorders are usually hormone induced and therefore usually seen in the reproductive period of life with dramatic fall in incidence after menopause. As compared to breast cancers, benign breast lesions are 10 times more common. The aim of the study was to determine the spectrum and incidence of various benign breast diseases in female patients attending our institute and to compare the results with those of other studies. Material and methods: 80 cases of benign breast diseases which were clinically diagnosed and confirmed pathologically or radiologically were subjected for therapeutic interventions and the results were analysed. Results: In the present study of 80 cases, the age group most affected by benign breast diseases was 21-30 years. 63 patients (78.8 %) presented with lump in the breast and 23 patients’ common symptom is pain. In most of the cases of lump had duration between 7-12 months (38.8 %), pain for 1-5 days (13.8 %), discharge for 0-5 days (11.3 %). Both breasts were involved in 6 cases (7.5 %) whereas right and left breasts are equally involved in 47 cases each (46.25 %). Most of the patients were nulliparous (46.3 %) followed by multiparous (38.8 %) and uniparous (15.0 %). Fibroadenoma constituted in 53.8 % of patients (44 cases), breast abscess constituted 21.25 % (17 cases). The most commonly affected age group was 21-30 years. 63 patients (78.8 %) presented with lump in the breast and 23 patients presented with pain. HRUSG findings correlated with that of clinical diagnosis in 70 cases. 60 cases underwent core biopsy, and in 41 cases (68.33 %) there were fibroadenoma and 7 cases (11.66 %) fibro adenosis. 59 cases (73.75 %) underwent excision, and 18 cases (22.5 %) incision and drainage. Conclusion: The most common benign breast disease was fibroadenoma. Most common age group affected with benign breast disease was 21-30 years. 88.7 % of clinical diagnosis, 90.3 % of radiological diagnosis, 93.3 % of core needle biopsy diagnoses were correlating with the histopathology diagnosis